Reducing supplementation frequency for Nellore beef steers grazing tropical pastures - Canesin, Roberta Carrilho [UNESP]; Berchielli, Telma Teresinha [UNESP]; Vega, Antonio de; Reis, Ricardo Andrade [UNESP]; Messana, Juliana Duarte [UNESP]; Baldi, Fernando [UNESP]; Pascoa, Adriano Gomes [UNESP] (Universidade de São Paulo (USP), 2014)
Reduced supplementation frequency is a broadly applied management practice. Ruminants consuming low quality forages/pastures, supplemented less than once daily are able to maintain body weight gain (BWG), efficiency of use of dry matter, nitrogen and other nutrients, as compared with animals supplemented once daily. We evaluated the feeding behavior, dry matter intake (DMI), dry matter and organic matter digestibility (DMD and OMD), BWG, Longissimus muscle area and backfat depth of Nellore steers raised on Brachiaria brizantha cv. Marandu pastures during the dry season, with different supplementation patterns. Thirty six animals (338 +/- 40.7 kg) were distributed over nine paddocks according to a completely randomized design. Treatments were based on supplementation frequency: once daily (OD), once daily except Saturdays and Sundays (SS), or on alternate days (AD), at 1.0%, 1.4% and 2.0% BW, respectively. Average total DMI accounted for 1.6 % BW day(-1), with no effect of supplementation frequency. Supplementation frequency had no effect on BWG or grazing time during the day. There was no difference in Longissimus muscle area animals supplemented daily, SS and AD. The backfat depth was thinner in animals supplemented AD, but even in this case, it was within the standards considered satisfactory for a finishing steer. Reducing supplementation frequency seems a good option to lower labor costs without affecting feed efficiency or carcass quality in beef cattle grazing tropical pastures.